MICROSOFT TEAM OF ZOOM AS A MEDIA FOR TEACHING EXTENSIVE READING DURING COVID 19 PANDEMIC - Fadilah, Fadilah; Rabi’ah, Rabi’ah; Baidawi, Achmad (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
Microsoft Teams is a cloud app digital hub that brings channels, conversations, meetings, files and apps to Microsoft 365. Extensive reading is a kind of subjects at English department which let the students to read the articles as they want to read for pleasure, the important thing, they can get some informations as the result of their reading. Therefore, they can explore by reading aloud, writing, speaking or other things related with finding new vocabulary or practicing a good pronounciation. In this case, they can choose to read newspaper, magazine, bulletine, reading drama script, reading poetry or many other articles. Therefore, using microsoft team by zoom will support the teaching and learning process in this pandemic with virtual class, because with this platform, it can encourage them reading ethusiasticly with their team by various responses. The objectives of this research are how the lecturer implement microsoft teams in teaching Extensive Reading during covid 19 pandemic and what the students’ response on using microsoft teams in teaching Extensive Reading druing virtual class. To answer those aims, the researcher conducted the research which is qualitative appoarch. The result from observation (that the researcher has joined online class directly by using microsoft team by zoom) and interview of WA chatting show that using microsoft team is really helpful in extensive reading class, because the students shew positive responsive,namely the creations that resulted from their readings show that they really read the article as they want to read and chose to explore the informations the got by speaking (a news broadcaster by sharelink the youtube, news teller) then writing by making resume of the innformations they have read.